2010
DOI: 10.1007/s11224-010-9676-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards physical interpretation of Hammett constants: charge transferred between active regions of substituents and a functional group

Abstract: The charges transferred between substituents and two functional groups: nitroso and N,N-dimethylamine in disubstituted benzene rings, were calculated at the B3LYP/cc-pVDZ level, using Natural Population Analysis. They were compared with the charges transferred between active regions of the substituents and of the groups. The transferred charge was well correlated with the Hammett constants, but only when the charges were calculated for the corresponding active regions instead of being calculated for the substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 62 publications
1
66
0
Order By: Relevance
“…Nevertheless, before going into detailed studies of SEs in meta-and para-substituted nitrobenzene derivatives by use of classical substituent constants (σ) and quantum chemistry based cSAR(X) [31][32][33] and SESE [29,30] characteristics we should determine their mutual interrelations.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, before going into detailed studies of SEs in meta-and para-substituted nitrobenzene derivatives by use of classical substituent constants (σ) and quantum chemistry based cSAR(X) [31][32][33] and SESE [29,30] characteristics we should determine their mutual interrelations.…”
Section: Resultsmentioning
confidence: 99%
“…By definition, cSAR(X) is a sum of atomic charges at all atoms of the substituent and the ipso carbon atom [7]. This descriptor correlates well with substituent constants [7][8][9][10]. It is important to stress that the cSAR(X) approach realized by the use of different atomic charge schemes leads to the results which are, as a rule, mutually well correlated [11].…”
Section: ) Is Alwaysmentioning
confidence: 99%
“…It has been shown that also charges transferred between the active regions of a functional group and of substituents correlate with substituent constants. Namely, we found such correlations of calculated qSAR(X)-qSAR(NO) in p-and m-substituted nitrosobenzenes and the values of r p or r m [22], where qSAR(NO) means the charge of the active region of the NO functional group. Therefore, we aimed to investigate whether the amount of the transfer in the excited singlet state of the two series of compounds, p-substituted benzoic acids and p-substituted nitrosobenzenes, also correlates with the Hammett constants.…”
Section: Introductionmentioning
confidence: 64%